Non‐invasive haemoglobin measurement as an index test to detect pre‐operative anaemia in elective surgery patients – a prospective study. (23rd November 2020) - Wittenmeier, E.; Paumen, Y.; Mildenberger, P.; Smetiprach, J.; Pirlich, N.; Griemert, E.‐V.; Kriege, M.; Engelhard, K.
Summary: Non‐invasive haemoglobin measurement using absolute values lacks the precision to be the sole basis for the treatment of pre‐operative anaemia. However, it can possibly serve as a screening test, indexing 'anaemia' with high sensitivity when values remain under prespecified cut‐off values. Based on previous data, non‐invasive haemoglobin cut‐off values (146 g.l −1 for women and 152 g.l −1 for men) detect true anaemia with 99% sensitivity. An index test with these prespecified cut‐off values was verified by prospective measurement of non‐invasive and invasive haemoglobin pre‐operatively in elective surgical patients. In 809 patients, this showed an estimated sensitivity (95%CI) of 98.9% (94.1–99.9%) in women and 96.4% (91.0–99.0%) in men. This saved invasive blood tests in 9% of female and 28% of male patients. In female patients, a lower non‐invasive haemoglobin cut‐off value (138 g.l −1 ) would save 28% of invasive blood tests with a sensitivity of 95%. The target 99% sensitivity would be reached by non‐invasive haemoglobin cut‐off values of 152 g.l −1 in female and 162 g.l −1 in male patients, saving 3% and 9% of invasive blood tests, respectively. Bias and limits of agreement between non‐invasive and laboratory haemoglobin levels were 2 and − 25 to 28 g.l −1, respectively. Patient and measurement characteristics did not influence the agreement between non‐invasive and laboratory haemoglobin levels. Although sensitivity was very high, the index test using prespecified cut‐off values just failed to reach the target sensitivity to detect true anaemia. Nevertheless, with respect to blood‐sparing effects, the use of the index test in men may be clinically useful, while an index test with a lower cut‐off (132 g.l −1 ) could be more clinically appropriate in women.